2011
DOI: 10.1038/eye.2010.232
|View full text |Cite
|
Sign up to set email alerts
|

Development of polypoidal lesions in age-related macular degeneration

Abstract: Purpose To investigate the development of polypoidal lesions using indocyanine green angiography (IA) in eyes with typical age-related macular degeneration (AMD). Methods We retrospectively reviewed the medical records of 47 consecutive patients (47 eyes) with typical AMD who had been followed up with IA for at least 2 years. Results At the initial visit, although all eyes showed classic and/or occult choroidal neovascularization (CNV) associated with AMD, no eyes showed polypoidal lesions by IA. However, duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…11 Abe et al 44 showed that the DLS is more prominent near "abnormal blood vessel networks" on ICGA, and Khan et al 45 discovered by means of simultaneous eyetracked spectral-domain OCT and ICGA that BVNs represent Type 1 neovascular tissue closely associated with PCV polyps. Although controversial, this and other evidence, [46][47][48][49][50] suggest that PCV may represent an end point of long-standing Type 1 CNV rather than a distinct maculopathy emanating from the pathologic features of the inner choroidal vasculature. 45 Fung et al 10 found that both aging patients with long-standing CSC and patients with clinical findings identical to our PPE patients (but without any history of classic CSC) may develop Type 1 neovascularization, similar to our PPE subjects who showed the DLS on OCT possibly representing early occult type neovascular tissue.…”
Section: Discussionmentioning
confidence: 90%
“…11 Abe et al 44 showed that the DLS is more prominent near "abnormal blood vessel networks" on ICGA, and Khan et al 45 discovered by means of simultaneous eyetracked spectral-domain OCT and ICGA that BVNs represent Type 1 neovascular tissue closely associated with PCV polyps. Although controversial, this and other evidence, [46][47][48][49][50] suggest that PCV may represent an end point of long-standing Type 1 CNV rather than a distinct maculopathy emanating from the pathologic features of the inner choroidal vasculature. 45 Fung et al 10 found that both aging patients with long-standing CSC and patients with clinical findings identical to our PPE patients (but without any history of classic CSC) may develop Type 1 neovascularization, similar to our PPE subjects who showed the DLS on OCT possibly representing early occult type neovascular tissue.…”
Section: Discussionmentioning
confidence: 90%
“…These differences may be responsible for the variation in treatment response and recurrence rate. To add to the complexity of this area, there are areas of overlap between AMD and PCV: classic CNV has been identified in some PCV cases, 36 whereas polypoidal lesions may also develop during follow‐up of eyes initially diagnosed with AMD 37 . Therefore, the current study documents angiographic details throughout a 1‐year follow‐up period and grade them with standard protocols to allow detailed analysis of features on both FA and ICGA.…”
Section: Discussionmentioning
confidence: 99%
“…As polypoidal lesions spontaneously resolve or regress with treatment, eyes with PCV can sometimes show only type 1 CNV without polypoidal lesions, which cannot be differentiated from tnAMD with type 1 CNV. In contrast, in Japanese patients, it has been demonstrated that 28% of eyes with tnAMD develop polypoidal lesions during the follow-up period of two years [ 39 ].…”
Section: Characteristic Findings In Imaging Analyses For Neovasculmentioning
confidence: 99%